2019
DOI: 10.5498/wjp.v9.i6.83
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and disasters: A systematic review

Abstract: BACKGROUNDDissociation, which is defined as the failure to associate consciousness, memory, identity, emotion, perception, body representation, motor control, and behavior into an integrated whole, has long been assumed to be generated by trauma. If dissociation is a product of trauma exposure, then dissociation would be a major mental health outcome observed in studies of disaster survivors. Although some studies have examined dissociation in disasters, no systematic literature reviews have been conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 125 publications
0
11
0
3
Order By: Relevance
“…Literatürde deprem ya da başka doğal afetler sonrası yaşanan dissosiyasyon ile ilgili çalışmalar yapılmıştır [25][26][27][28] . Haiti 2010 yılı yaşanan deprem sonrası hayatta kalan kişiler ile yapılan bir çalışmada katılımcılara PTSB semptom kontrol listesi ve peritravmatik disosiyasyon ölçeği uygulanmıştır.…”
Section: İstatistiksel Analizunclassified
“…Literatürde deprem ya da başka doğal afetler sonrası yaşanan dissosiyasyon ile ilgili çalışmalar yapılmıştır [25][26][27][28] . Haiti 2010 yılı yaşanan deprem sonrası hayatta kalan kişiler ile yapılan bir çalışmada katılımcılara PTSB semptom kontrol listesi ve peritravmatik disosiyasyon ölçeği uygulanmıştır.…”
Section: İstatistiksel Analizunclassified
“…dictatorships) stress. This is especially noticeable when circumstances and the future are unpredictable, unforeseeable, in which case people are even more precarious in a state of loss of control [15]. For example, Brooks et al [16] found that an o cially ordered quarantine or lockdown may be a measure that signi cantly increases an individual's level of perceived stress, which may affect the experienced dissociative symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Subjective disaster-related stress can be assessed by measuring peritraumatic distress and peritraumatic dissociative experiences. [23][24][25] These responses at the time of the event are often measured retrospectively. 25,26 Peritraumatic dissociation is considered a mechanism intended to cope with severe trauma, shielding the individual from overwhelming emotions during and/or after the traumatic event through derealization and altered awareness.…”
Section: Introductionmentioning
confidence: 99%
“…27 Both peritraumatic distress and dissociation were found to be robust contributing factors toward the development of post-traumatic stress disorder (PTSD)-like symptoms and depression, two psychopathologies with extensive overlap in symptomatology, risk factors, and comorbidities. 23,25,28 Psychological resilience is thought to be a major moderator of the relationship between the experience of trauma and the development of post-traumatic psychopathology. 29,30 In this context, resilience is thought of as a dynamic process, the capacity to bounce back, cope with, and recover from adverse events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation